PERLINDUNGAN HUKUM PENGGUNA LAYANAN OJEK ONLINE OLEH PT GRAB INDONESIA CABANG BUKITTINGGI - Silfi Gustria; Nuzul Rahmayani; Mahlil Adriaman (Ensiklopedia of Journal, 2023)
The purpose of this research is to find out and analyze the obstacles faced by PT Grab Indonesia, as well as efforts made to overcome the obstacles encountered at the Bukittinggi branch. This research is analytical descriptive in nature, meaning that this research aims to provide data about a situation or social phenomena that develop in the midst of society in accordance with facts and without engineering, so that with this research it is hoped that it will be able to obtain a comprehensive, complete and systematic picture of object under study. This type of research uses empirical juridical research, namely data and facts obtained in the field and then researched and developed based on law. Obstacles faced by GrabBike service users in the city of Bukittinggi include the application being too complicated to understand in its use for some Grab service users, tariffs changing and starting to become unaffordable for some users, Grab service provider partners who do not meet standard equipment in carrying out activities that have been determined by Grab. The efforts that can be made to overcome the obstacles faced include; Grab service users when using the service are required to search, read and follow the instructions for using the application, PT. Grab Indonesia also needs to update a simpler application so that it is easier to understand and can be used by all groups and legal protection in the form of preventive and repressive.